Chlorophyll, primary production, and organic carbon fluxes in the Kara Sea. - Vetrov, Alexander A (PANGAEA, 2008)
New maps of mean monthly distribution of chlorophyll and primary production in the Kara Sea were compiled using joint processing of CZCS (1978-1986), SeaWiFS (1998-2005), and MODIS (2002-2006) satellite data and field measurements. The annual primary production of phytoplankton is estimated at 22.3 x 10**6 t C per year or 70 mg C/m**2 per day. Results of calculations of the organic carbon budget in the Kara Sea are presented.
(Table 1) Contents of chlorophyll a over the Northern Sea Route according to data of field measurements and estimated from MODIS data on measurement days
Keywords: Archive of Ocean Data; ARCOD; Chlorophyll a; Date/Time of event; Kara Sea; Lena River estuary; Pechora Sea (southeast Barents Sea); Vetrov-2008-1; Vetrov-2008-10; Vetrov-2008-11; Vetrov-2008-12; Vetrov-2008-13; Vetrov-2008-14; Vetrov-2008-15; Vetrov-2008-16; Vetrov-2008-17; Vetrov-2008-18; Vetrov-2008-19; Vetrov-2008-2; Vetrov-2008-20; Vetrov-2008-21; Vetrov-2008-22; Vetrov-2008-23; Vetrov-2008-3; Vetrov-2008-4; Vetrov-2008-5; Vetrov-2008-6; Vetrov-2008-7; Vetrov-2008-8; Vetrov-2008-9; White Sea; White Sea off Belomorsk